Splenic cystic lymphangioma in adult: a case observed in the Visceral Surgery Department II of Mohamed V Military Hospital - Rebbani, Mohammed; El Brahmi, Yasser; El Mouhafid, Failsal; Ait Ali, Abdelmounaim; Zentar, Aziz (International Surgery Journal, 2020)
Cyctic lymphangioma is a primary benign tumor due to congenital malformations of the lymphatic vessels. It is more often seen in pediatric patients and the usual site for lymphangioma is the cervical and axillary region. However, it is exceptionally seen in adults and involving rarely the spleen. The discovery of the splenic lymphangioma is generally accidental during imaging performed for another pathology. Indeed, being most often asymptomatic, the clinical presentation of cystic lymphangioma is polymorphic and it is related generally to mass effects. In this paper, we report the case of a 43 years old patient in whom the discovery was fortuitous during imaging for a non-specific symptomatology. The physical examination was normal and magnetic resonance imaging strongly evoked the diagnosis of cystic lymphangioma. A total splenectomy was performed and the histological examination has confirmed the positive diagnosis of splenic lymphangioma. Finally, this case confirmes that the diagnostic of splenic lymphangioma should be evoked in front of splenic cystic lesions and the confirmation and the differential diagnosis are made by histopathology and immunohistochemistry studies.